Conversion of recycled indigo from waste blue jeans into indirubin anticancer drug - Yeo, Chan Seo; Yuk, Yong; Jang, Ji Hwan; Pagolu, Raviteja; Choi, Kwon Young (Chemosphere, 2025)
In this study, the optimal production of indirubin and conversion of indigo extracted from waste blue jeans into indirubin, a precursor for anticancer drugs, are presented. Indirubin shares the same biosynthetic pathway as indigo, a dye commonly used in the production of jeans, but is synthesized through asymmetric dimerization. During this process, 2-oxoindole and isatin function as key precursors. Various conditions, including the T4MO enzyme, surfactants, bioconversion reactions, and the extraction solvent, were optimized to achieve efficient indirubin production. A major challenge in this process is the simultaneous production of both indigo and indirubin. Considering that indigo has lower photostability compared to indirubin, and its photodegradation yields isatin—a precursor for indirubin biosynthesis—the possibility of converting indigo to indirubin via photodecomposition was explored. This innovative approach was successfully validated. As a result, a yield of 5.95 mg of indirubin per pair of jeans was achieved through a bioconversion process, in which indigo was extracted from waste jeans and subsequently converted to indirubin following light-induced decomposition. This research demonstrates the potential for recycling waste jeans through an upcycling process, turning them into valuable precursors for anticancer drug development.
Keywords: Anticancer drug; Biosynthetic pathway; Blue jeans; Indigo; Indigo degradation; Indigo upcycling; Indirubin; Isatin; Optimal production; Waste blue jean; Antineoplastic Agents; Coloring Agents; Indigo Carmine; Indoles; Photolysis; Recycling; Indigo; Indigo degradation; Indigo upcycling; Indirubin; Isatin; Waste blue jean